The Evolution of the Ennahda Movement: From Religious Ideology to Political Force in Tunisia's Post-Revolution Era - Sundus Serhan Ahmed (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This article examines the ideological and political transformation of Tunisia’s Ennahda Movement from a clandestine Islamist organization inspired by the Muslim Brotherhood into a central actor in Tunisia’s post-revolutionary democratic landscape. The research addresses how Ennahda redefined its political identity in response to shifting sociopolitical conditions following the 2011 revolution. Employing qualitative methods—including thematic, discourse, and comparative analysis—the study draws on primary data such as party manifestos, speeches by Rached Ghannouchi, and interviews with political actors, as well as secondary scholarly sources. The findings indicate that Ennahda’s transformation was not merely rhetorical but entailed significant changes in discourse, institutional behavior, and strategic orientation, especially in adopting a “Muslim Democratic” identity. However, the study argues that this transformation was primarily driven by political necessity rather than a fundamental ideological shift. The article highlights the internal and external challenges faced by Ennahda in balancing religious legitimacy, democratic engagement, and coalition politics. It contributes to the broader discourse on political Islam by illustrating how Islamist movements adapt to democratic transitions in pluralistic societies.